Mythical Notion of the Children’s Diseases and Their Liminal Expression in the Traditional Lithuanian Worldview - Džekčioriūtė-Medeišienė, Vita (Tautosakos darbai, 2022)
Children’s diseases in the Lithuanian folk medicine have not been coherently investigated so far. This article focuses on the mythical notion of the children’s diseases in the traditional Lithuanian worldview. The study embraces the period from the end of the 19th century to the first half of the 20th century. The author of the article scrutinizes folklore and ethnographic data that gives evidence of the folk medicine practices reflecting the mythical view of the human body and its ailments.The main supporting axis of the study rests on the boundaries and their symbolic expression. In folk medicine, when establishing notion of the diseases and various healing practices, boundaries can be drawn in various ways: as the body boundaries, as the boundaries of the surrounding spaces, time boundaries or those introduced by the liminal states and rites of passage. The manifestation of these boundaries in terms of the children’s diseases is exhibited in the article by exemplifying three children’s ailments typical to the folk medicine: bristles, whooping cough, and moonlight. Analysis of their etiology, symptoms and healing methods proves that in case of bristles, the liminal expressions employ the body boundaries (i. e. skin) and those related to the rites of passage (i. e. pregnancy); whereas in case of whooping cough and moonlight, the liminal expressions of time, space and body boundaries are relevant. Bristles tend to be envisaged as a disease without a personified shape, while whooping cough and moonlight are pictured as some mythical beings that can be addressed and mislead.
Keywords: children’s diseases; folk medicine; boundaries; bristles; whooping cough; moonlight